The perception of effectiveness of training methods on retail employee performance: A proposed model - Ajmir Singh , Sokuan Singh; Abdullah, Khairul Hafezad; Mahmud , Luqman (International Journal of Accounting, Finance and Business, 2026)
This study investigates the impact of various training methods such as classroom training, e-learning, and on-the-job training on employee performance within the dynamic context of retail business. Recognizing human capital as a central organizational asset, Business Retails has invested significantly in training to enhance productivity, adaptability, and service quality amid an evolving retail landscape. However, inconsistent employee performance, particularly post-pandemic, raises concerns about the effectiveness and relevance of these training initiatives. Grounded in the Blended Learning Theory, this research explores employee perceptions of different training modalities and their correlation with measurable job performance outcomes. By analyzing how these perceptions influence learning engagement and practical skill application, the study aims to identify optimal training strategies that drive performance improvement. Findings will contribute to both academic understanding and practical insights, helping Retail organizations align training delivery with workforce needs, maximize training ROI, and foster sustained employee development in a competitive retail environment.